ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA GRATIFIKASI (Studi Putusan Nomor 18/Pid.Sus-TPK/2017/PN.Tjk) - Erniyati Erniyati; D. Novrian Syahputra; Riko Herdiansah (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2022)
Social phenomenon is still going on cases of criminal gratification that need to be optimized law enforcement in the field of the field. One of them is gratification crime of making land sale and purchase documents in Case Number: 18 / Pid.Sus-TPK / 2017 / PN.Tjk. The results of the study and discussion show that the factors causing the perpetrators of gratification crime on Decision Case Number 18 / Pid.Sus-TPK / 2017 / PN.Tjk include: intrinsic and extrinsic factors, lack of supervision of the use of funds, the gap to mark up all costs projects, lack of accountability and transparency of budget usage, lack of community control, nepotism-influenced governance structures. Criminal liability of perpetrators of gratification crime based on Case Decision Number 18 / Pid.Sus-TPK / 2017 / PN.Tjk implemented by punishment against Defendant. The judges shall impose a 1 (one) year imprisonment and a fine of Rp 50,000,000.00 (five million rupiahs) on the condition that the unpaid penalty may be replaced by a one-month imprisonment. Legal status of evidence against gratification crime pursuant to Decision Case Number 18 / Pid.Sus-TPK / 2017 / PN.Tjk that is in accordance with the court decision that the evidence in the form of document of evidence proof letter remain attached in file case, to the Defendant while goods butki Cash Rp. 25.000.000, - shall be returned to the eligible as stated in Court Decision. Keywords: Criminal Responsibility, Crime, Gratification